The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1051/kmae/2011050
|View full text |Cite
|
Sign up to set email alerts
|

Influence of wastewater on zooplankton communities in the Daugava River upstream and downstream of Daugavpils over the last 50 years

Abstract: During expeditions to the section of the Daugava River from Surozha in Belarus to Dunava in Latvia in 2008, and during expeditions to the Kraslava-Dunava section in 2009, zooplankton were sampled. Quantitative characteristics, the relation of zooplankton taxonomic groups, the saprobity index and species diversity (Shannon-Wiener index) were employed for the analysis of zooplankton community structure in the Daugava River. The results were compared with the Daugava zooplankton findings of the research carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…When the water level began to recede, the impact of wastewater pollution on fish abundance and species richness became much more apparent. Evidence of similar impacts of wastewater on zooplankton, the key natural food for many of the fishes, during low water level is available (Deksne, 2011).…”
Section: Spatial and Temporal Changes In Fish Community And Water Quamentioning
confidence: 99%
“…When the water level began to recede, the impact of wastewater pollution on fish abundance and species richness became much more apparent. Evidence of similar impacts of wastewater on zooplankton, the key natural food for many of the fishes, during low water level is available (Deksne, 2011).…”
Section: Spatial and Temporal Changes In Fish Community And Water Quamentioning
confidence: 99%
“…Biological oxygen demand (BOD 5 ) recorded high levels, ranging from 1.3 mg/L in the second site to 8.1 mg/L in the fourth, which is a negatively determining effect on zooplankton [39]. This implies that the river water is questionable in its cleanliness.…”
Section: Calculating the Value Of The Water Quality Indexmentioning
confidence: 99%
“…While, the values were from 42 (Poor) to 65 (Fair) during different seasons. As for drinking usages, the results demonstrated poor or undrinkable (31)(32)(33)(34)(35)(36)(37)(38)(39)(40) water in all sites. Meanwhile, the values ranged from 39 (Poor) to 56 (Clear) in regard to seasons.…”
mentioning
confidence: 94%
“…Another exception is a study of the zooplankton of the middle Parana River (Argentina) between 1971 and 2007, which found that rotifer numbers declined significantly after 1999 and that there was growing evidence that levels of competition between rotifers and cladocerans were increasing (de Paggi et al 2014). One final example is that of Deksne (2011Deksne ( ), who analysed data collected between 1962Deksne ( and 1968Deksne ( , and between 2005Deksne ( and 2009, from the Duagava River, which lies between Belarus and Latvia. Again, the dominant group of zooplankton in the river was rotifers, and it was noted that there was a tendency for the species diversity of zooplankton in this river to decrease over time.…”
Section: Insights Into the Effects Of Environmental Change On Rotifer Populationsmentioning
confidence: 99%
“…These authors found that, although most zooplankton species had remained relatively stable, rotifers had declined markedly (from 40% to 4% of total zooplankton biomass) over the previous 40 years although the reason was unclear. In a study that demonstrated a different response of rotifers to pollution, Deksne (2011) investigated the influence of wastewater on zooplankton of the Duagava River (Balrus/Latvia) by comparing data collected between 1962 and 1968 with that collected between 2005 and 2009 (i.e. before and after a new wastewater treatment plant had been installed).…”
Section: Changes In Water Quality and Quantitymentioning
confidence: 99%